2019
DOI: 10.1155/2019/8074096
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Different Positions and Angles of Implants in Maxillary Edentulous Jaw on Surrounding Bone Stress under Dynamic Loading: A Three-Dimensional Finite Element Analysis

Abstract: Purpose. To evaluate the effects of different placements of mesial implants and different angles of distant implants in maxillary edentulous jaws on the stress on the implant and the surrounding bone tissue under dynamic loading. Materials and Methods. Cone beam computed tomography was used to acquire images of maxillary edentulous jaws. Using Mimics 17.0, Geomagic, and Unigraphics NX8.5 software, three-dimensional models were established: two mesial implants were placed vertically in the anterior region of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
19
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 29 publications
(33 reference statements)
4
19
0
2
Order By: Relevance
“…This finding is consistent with the study of previous authors [24], who found that cantilever loading had a large effect on bone stress. Increased bone stress can increase the risk of implant loss due to bone overload [12].…”
Section: Preprintssupporting
confidence: 94%
See 1 more Smart Citation
“…This finding is consistent with the study of previous authors [24], who found that cantilever loading had a large effect on bone stress. Increased bone stress can increase the risk of implant loss due to bone overload [12].…”
Section: Preprintssupporting
confidence: 94%
“…The results obtained in the present study also indicated that anterior cantilever loading can negatively affect the implant stress magni- implants. Although this stress check exists in several previous studies [12,[20][21][22][23][24][25][26] they did not considered different implant positions as the present models. The literature [20][21][22][23][24][25][26][27] usually reports the maximum forces capable of generating mechanical problems in the bone-implant interface, however, there are no reports showing the cantilever in anterior region similar to this study.…”
Section: Preprintsmentioning
confidence: 99%
“…The survival of implants with All‐on‐4 concept is well documented and accepted throughout the community of implantologist (Liu et al, 2019; Taruna et al, 2014). However, the degree of implantation of distal abutment is yet to be explored (Liu et al, 2019; Ozan & Kurtulmus‐Yilmaz, 2018; Saber et al, 2015). Moreover, crestal bone loss in the micro‐region of mesial and distal implants has not been reported so far.…”
Section: Discussionmentioning
confidence: 99%
“…Setting implants at a certain angle cantilevers may be reduced. Tilted implants may help to refuse large lateral and vertical bone augmentation, nerve lateralization and sinus lift with all leading risk of complications (Krekmanov et al, 2000; Liu et al, 2019). Moreover, the procedure allows longer implants where bone‐to‐implant contact is increased, providing primary stability.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation